Virtual immortality - god, evolution and the singularity in Post- and Transhumanism - Krüger, Oliver (Kulturen der Gesellschaft, 2021)
In recent years, ideas of post- and transhumanism have been popularized by novels, TV series and Hollywood movies. According to this radical perspective, humankind and all biological life have become obsolete. Traditional forms of life are inefficient to process information and too inept at crossing the high frontier: outer space. While humankind can expect to be replaced by their own artificial progeny, post-humanists assume that they will become an immortal part of a transcendent superintelligence. Kruger's award-winning study examines the historical and philosophical context of these futuristic promises by Ray Kurzweil, Nick Bostrom, Frank Tipler, and other posthumanist thinkers.